The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.9734/jenrr/2023/v13i1254
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Charcoal Briquettes Fuel from a Blend of Coconut Husk and Corncob

Abstract: Energy is very essential to human livelihood and makes significant help to economic, social, and environmental features of human development. Biomass is certainly a very significant source of renewable energy worldwide and abundant with high energy potential. This research aimed to characterize and produce briquette fuel from the combination of coconut husk and corncob using starch as a binder. The composite briquettes were produced by varying the mixture ratio of coconut husk to corncob (CH: CC), 80:20, 60:40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…This value is within the acceptable limit of 5-4 wt% for solid biomass [27][28]. It is also in line with 3.4% -4.9% from non-woody biomass by Babajide et al [24], and lower than the value from Jirijor et al [19] which recorded 4.53% -10.12% for nonwoody biomass. High ash content is detrimental to combustion and leads to fire management problems, such as regularly removing ash from the stove.…”
Section: Ash Contentsupporting
confidence: 84%
See 2 more Smart Citations
“…This value is within the acceptable limit of 5-4 wt% for solid biomass [27][28]. It is also in line with 3.4% -4.9% from non-woody biomass by Babajide et al [24], and lower than the value from Jirijor et al [19] which recorded 4.53% -10.12% for nonwoody biomass. High ash content is detrimental to combustion and leads to fire management problems, such as regularly removing ash from the stove.…”
Section: Ash Contentsupporting
confidence: 84%
“…The results of testing of the equipment revealed that the highest binder concentration ratios of 30% and 40% produced the best result. Yirijor et al [19] assessed the physical and mechanical properties of briquettes produced from dry coconut husk tagged "CNH" and cocoa pod tagged "CCP" Ghana. The agro-waste was gathered, carbonised at 450 o C carbonizing temperature.…”
Section: Classification Of Biomass Briquetting Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample A generated a better calorific value at 18704.1 Kj/Kg while sample B had a calorific value of 18901.3 Kj/Kg. Although both results are a bit lower than the reported value for wood fuels in Iyer et al [14], but they are far better than minimum heating value for briquette production [19,20,21]. Sample B has a higher calorific value when compared to sample A as well as a better combustion characteristics.…”
Section: Bulk Densities and Calorific Valuesmentioning
confidence: 58%
“…Combustion refers to the conversion of biomass to heat and power by directly burning it, as occurs in boilers. Gasification is the process of converting solid biomass with a limited quantity of air into producer gas, while pyrolysis is the thermal decomposition of biomass in the absence of oxygen" [1][2].…”
Section: Introduction 11 Background Of Studymentioning
confidence: 99%